Simple and rapid fabrication of Na0.5K0.5NbO3 thin films by a chelate route - Fernández Solarte, Alejandra María (2013)
Na0.5K0.5NbO3 (NKN) thin films were prepared by a chelate route which offers the advantage of a simple and rapid solution synthesis. The route is based on the use of acetoin as chelating agent. The process was optimized by investigating the effects of alkaline volatilization on film properties. While we observed no evidence of stoichiometry problems due to potassium volatilization loss during the heat treatments, thin films synthesized with insufficient sodium excess presented a potassium rich secondary phase, which has a significant influence on the ferroelectric properties. We show that the amount of spurious phase decreases with increasing Na+ concentration, in such a way that a 20 mol% Na+ excess is necessary to fully compensate the volatilization loss occurred during the heat treatment. In this way, NKN thin films annealed at 650ºC presented a well crystallized perovskite structure, no secondary phases, well-defined ferroelectric hysteresis loops (Pr ~ 9 μC/cm2, Ec ~ 45 kV/cm), and low leakage current density (2 × 10−7 A/cm2 at 80 kV/cm).